Control quimico de Oligonychus punicae (ARAÑITA MARRÓN) EN Persea americana MILLER VARIEDAD HASS, EN LAMBAYEQUE - Cruzado Padilla, Fernando Ysmael (2011)
Between the months of January and April (summer) of year 2011 a work of field with the aim of describing was realised as the Agrícola company Cerro Prieto S.A.C. comes carrying out the chemical control for the acarus Oligonychus punicae (arañita brown) in the culture from avocado var. Hass, of 1,5 years. The densidad of the orchard was of 666 trees by has. ; with irrigation by dripping. The used products were registered for this culture and the use of each was based on a threshold of action established by the company and its application depended on the percentage (%) and degree (g) of infestation of the acarus. The used products were: a mixture of an agricultural detergent out dust 200 cc/cil + an agricultural oil known commercially like biol 200 cc/cil, used for washings when there is presence of brown arañita and a product with sulphur micronizado with lime, preparation in the denominated company sulfocalcio in 6 doses of lts/cil, applied product when % of infestation of leaves surpass 8% (24 infested leaves) and the G of infestation of adults and nymphs this in G: 1 (1 to 5 individuals by leaf). The applications were realised by means of a tractor pistol, with adjustable pistols and personnel of field (12 gunmen by tractor pistol). The 250 pressures were lb/pul2 in the case of washings and 150 lb/pul2 in the case of the application of sulfocalcio, with volumes of 1000 Lts/ha. and 400 Lts/ha., respectively. The results indicate that sulfocalcio controlled populations of 12% of infestation maintained and them below the damage threshold (8%), and was not necessary to apply acaricidas as it shows the established threshold to it. In the case of the washings with high pressure with more detergent oils < could only be controlled low populations (; to 2% of infestation) of the acarus.